Beyond access to basic services: perspectives on social health determinants of Mozambique. Issue 5 (20th October 2021) - Llop-Girones, Alba; Jones, Sam
ABSTRACT: A wide range of evidence shows systematic differences in health status among social groups, which are associated with unequal exposure to and distribution of the social determinants of health (SDH). However, the role of these SDH has not been studied extensively in low-income countries, where most studies focus on access to medical care. In this paper, we undertake a retrospective cross-sectional analysis of the SDH in Mozambique for the period 2002–2014 based on a set of household budget surveys, covering 152, 259 observations. We run logistic regression models, comparing various sets of determinants of health status proxied by two measures: self-assessed overall health and number of days ill. The results, which include models stratified by sex, age and year, consistently show that neither better access to healthcare nor material conditions are related to better health. Rather, macro factors, proxied by place of residence, are the dominant predictor of health inequalities. In the stratified models, women and elders appear more vulnerable to poor health. The policy implication is that a narrow focus of health policy on selected services ignores the underlying economic and social context and their role in producing well-being or poor health. More integrated approaches are required to address the health equity gap in low-income countries.